Therapeutic Plasma Exchange in G6PD Deficient Patient Complicated with Intravascular Hemolysis: A Case Report - Esra Ermis Turak (Erciyes Medical Journal, 2020)
Glucose-6-phosphate dehydrogenase is an enzyme that protects the erythrocytes against oxidative damage. G6PD deficiency is a common disorder in Gulf Countries that may present with hemolytic anemia and acute renal failure after exposure to oxidative triggers, such as drug, infection or some foodstuffs. In this study, a severe and complicated case of a G6PD deficient patient was presented. A 65-year old G6PD deficient patient presented with acute renal failure and intravascular hemolysis after eating fava beans. Therapeutic plasma exchange was used in the patient for two consecutive days. Clinical and laboratory findings were improved with plasma exchange. Although supportive therapy is enough for mild cases, therapeutic plasma exchange can be life-saving in complicated cases.